2019
DOI: 10.1002/jclp.22830
|View full text |Cite
|
Sign up to set email alerts
|

Expressive suppression mediates the relation between disordered eating and suicidal ideation

Abstract: Objective Although disordered eating is robustly associated with suicidal thoughts, it is not well understood why these conditions relate to each other. Emotion dysregulation is a shared risk factor for disordered eating and suicidal thoughts. Individuals with dysregulated emotions struggle to select appropriate strategies to modulate emotions and the strategies they use might explain some of the shared variances. Thus, we examined whether emotion regulation strategies mediated the relationship between disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…There are some studies that indicate that the cost of suppression is dependent on factors such as how burdensome [21] or inauthentic [22] it feels to suppress one's feeling. Regardless, suppression is viewed overall as a costly emotion regulation strategy that is associated with negative health outcomes [23,24].…”
Section: Emotion Regulation Strategiesmentioning
confidence: 99%
“…There are some studies that indicate that the cost of suppression is dependent on factors such as how burdensome [21] or inauthentic [22] it feels to suppress one's feeling. Regardless, suppression is viewed overall as a costly emotion regulation strategy that is associated with negative health outcomes [23,24].…”
Section: Emotion Regulation Strategiesmentioning
confidence: 99%
“…Failure to adhere to exercise and diet regimens typically result in intense anxiety and guilt, and immediate attempts at compensation, including extra workout sessions, stricter dieting, or purging behaviors (Mangwetheth et al, 2001). Notably, research has found compulsive exercise is related to attempting suicide while eating concerns and purging behavior may increase risk for suicidal ideation (Ortiz et al, 2019; Portzky et al, 2014; Selbyy et al, 2010; Smithh et al, 2013). In sum, these shared symptoms that are found to increase risk of suicidality in BDD and EDs may similarly increase suicide risk in MD.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cross-sectional studies found no significant association between TCQ-R scores and an SI history (Titus & DeShong, 2020), even when modifying the items to focus on suicidal thoughts (e.g., “I analyze whether ending my life is rational”; Tucker et al, 2017, p. 39). Similarly, ERQ-R scores were not significantly associated with an SI history (Brausch et al, 2022; Forkmann et al, 2014; Ortiz et al, 2019) and did not predict daily SI severity over the course of 28 days (Franz et al, 2021). Therefore, state and trait-like cognitive reappraisal appear to have differential associations with SI severity.…”
Section: Resultsmentioning
confidence: 89%